Plane wave acoustic superposition for fast ultrasound imaging - Bodnariuc, Ecaterina; Schiffner, Martin Friedrich; Petra, Stefania; Schnörr, Christoph (2016 IEEE International Ultrasonics Symposium (IUS), 2016)
We introduce a novel method for ultrasound plane wave imaging that combines the plane wave decomposition of the incident pulse with the exact solution for the scattered field from small spherical scatterers. We model the measured RF-signal by a sparse linear system and formulate a corresponding discrete inverse problem, that can accommodate various types of regularization. The framework is demonstrated on undersampled phantoms from the PICMUS2016 [1] challenge.